Phosphate induces inflammation and exacerbates injury from cigarette smoke in the bronchial epithelium - Seth Bollenbecker; Kylie Heitman; Brian Czaya; Molly Easter; Meghan June Hirsch; Shia Vang; Elex Harris; E. Scott Helton; Jarrod W. Barnes; Christian Faul; Stefanie Krick (Scientific Reports, 2023)
Abstract An elevation in serum phosphate—also called hyperphosphatemia—is associated with reduced kidney function in chronic kidney disease (CKD). Reports show CKD patients are more likely to develop lung disease and have poorer kidney function that positively correlates with pulmonary obstruction. However, the underlying mechanisms are not well understood. Here, we report that two murine models of CKD, which both exhibit increased serum levels of phosphate and fibroblast growth factor (FGF) 23, a regulator of phosphate homeostasis, develop concomitant airway inflammation. Our in vitro studies point towards a similar increase of phosphate-induced inflammatory markers in human bronchial epithelial cells. FGF23 stimulation alone does not induce a proinflammatory response in the non-COPD bronchial epithelium and phosphate does not cause endogenous FGF23 release. Upregulation of the phosphate-induced proinflammatory cytokines is accompanied by activation of the extracellular-signal regulated kinase (ERK) pathway. Moreover, the addition of cigarette smoke extract (CSE) during phosphate treatments exacerbates inflammation as well as ERK activation, whereas co-treatment with FGF23 attenuates both the phosphate as well as the combined phosphate- and CS-induced inflammatory response, independent of ERK activation. Together, these data demonstrate a novel pathway that potentially explains pathological kidney-lung crosstalk with phosphate as a key mediator.